Unraveling the identity of Paepalanthus decorus (Eriocaulaceae) - Da Silva, Lucas Espindola Florêncio; Trovó, Marcelo (Phytotaxa, 2021)
Paepalanthus decorus was described by Delia Abbiatti from a single collection of individuals made by Carlos Luis Spegazzini in Uruguaiana, Rio Grande do Sul state, Brazil, deposited at the La Plata Museum. The species is known only from the type specimens, which were unusual for being collected far to the south of the distribution of the other species included in P. sect. Diphyomene. In recent nomenclatural treatments for P. sect. Diphyomene, P. decorus was disregarded, remaining known only from its original publication. Here, we critically evaluate the protologue, type specimens, and the vegetative and floral morphology of this species. As a result, we propose its synonymization under P. flaccidus. A detailed comparison of these species is provided, along with comments on typification, with a lectotype designated for P. flaccidus.